Mandible bone density in adolescents with cerebral palsy using antiepileptic drugs - Pavanello, Andrea; David, Antonio Francisco; Ferreira Costa, Andre Luiz; Botti Rodrigues Santos, Maria Teresa (Brazilian Dental Science, 2022)
Objective: The aim of this study was to assess the bone density of the mandible in adolescents with cerebral palsy(CP) treated with antiepileptic drugs using one beam computed tomography (CBCT). Methods: The study wascarried out with 18 adolescents aged 12–18 years, undergoing routine dental treatment at the dental clinic ofAPCD-São Caetano do Sul. CBCT scans were of divided into two groups: G1 adolescents with CP using antiepilepticdrugs and G2 normoactive adolescents. A single dentomaxillofacial radiologist assessed and evaluated the imagesusing Dental Slice software and Image J. Fisher’s exact tests as well as paired and unpaired Student’s t-testswere performed. Results: Groups differed significantly with regard in the values of density (p < 0.001), withG1 presenting lower values compare to G2. G1 showed significantly lower density means on the right side, leftside, and right/left sides of the mandible edge than G2 (p < 0.001). Conclusion: CP patients using antiepilepticdrugs show evidence of bone mineral density loss of the mandible.KEYWORDSAntiepileptic drugs; Bone mineral density; Cone beam computed tomography; Mandibular indices; Osteoporosis.